Constitutional Court Decision No. 90/PUU-XXI/2023 In the Dynamic Quo Vadis of Indonesian Law Rechtsstate of Machtsstate - Mulyadi, Dedi; Megawati, Leny (Intellectual Law Review (ILRE), 2024)
The birth of the decision of the Constitutional Court (MK) in adjudicating case Number: 90/PUU-XXI/2023 resulted in suspicion from many parties towards the President as the decider of the Constitutional Court's decision considering that the Chief Justice of the Constitutional Court is the President's brother-in-law or there were indications and/or suspicions that the Constitutional Court was intervened by the Presidential institution, and culminated in the formation of the Constitutional Court Honorary Council (MKMK). The Constitutional Court Judge's decision can be categorised as a decision that has the character of a Rechtsstate (rule of law) or actually confirms the Constitutional Court's decision that has the characteristics of a Machtstate (state of power) and the impact (Social, Political and Institutional Credibility) of the Constitutional Court's Decision on the Independence and Professionalism of the Constitutional Court Judges institutionally. This research uses normative juridical methods using secondary data in the form of literature studies. The aim of this research is to analyse the decisions of Judges and drug consumers as well as the Impact (Social, Political and Institutional Credibility) of Constitutional Court Decisions on the institutional Independence and Professionalism of Constitutional Court Judges. The research results show that the Constitutional Court Decision NO. 90/PUU-XXI/2023 is not in line with the third principle of the rule of law/Rechtsstaat, but the Constitutional Court's decision can be seen as a decision that has the dimension of state power (Machtstate).